2020
DOI: 10.2147/ijn.s239172
|View full text |Cite
|
Sign up to set email alerts
|

<p>Noninvasive Molecular Imaging of the Enhanced Permeability and Retention Effect by <sup>64</sup>Cu-Liposomes: In vivo Correlations with <sup>68</sup>Ga-RGD, Fluid Pressure, Diffusivity and <sup>18</sup>F-FDG</p>

Abstract: Background The accumulation of liposome encapsulated chemotherapy in solid cancers is dependent on the presence of the enhanced permeability and retention (EPR) effect. Positron emission tomography (PET) imaging with a liposome encapsulated radioisotope, such as liposome encapsulated Cu-64 ( 64 Cu-liposome) may help to identify tumors with high liposome accumulation, and thereby stratify patients based on expected benefit from liposomal chemotherapy. However, intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Børresen et al 64 recently investigated the correlation between the degree of the EPR effect ( 64 Cu-liposome) and tumor neoangiogenesis ( 68 Ga-RGD), fluid pressure, glycolytic activity ( 18 F-FDG) and diffusivity (diffusion-weighted MRI) to identify potential biomarkers suitable for prediction of the EPR effect in cancer models. The researchers determined that 64 Cu-liposome and 68 Ga-RGD uptake were moderately correlated, and the authors ultimately concluded only that 68 Ga-RGD does not qualify as a surrogate marker, and that 18 F-FDG (metabolic activity) and 64 Cu-liposome uptake were not correlated. Lee et al 65 introduced 64 Cu-MM-DX-929 (untargeted, no-drug PEGylated liposome) as a universal companion diagnostic agent to prospectively select patients for liposomal therapeutics.…”
Section: Liposomes Theranostic Applications and Diagnostic Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Børresen et al 64 recently investigated the correlation between the degree of the EPR effect ( 64 Cu-liposome) and tumor neoangiogenesis ( 68 Ga-RGD), fluid pressure, glycolytic activity ( 18 F-FDG) and diffusivity (diffusion-weighted MRI) to identify potential biomarkers suitable for prediction of the EPR effect in cancer models. The researchers determined that 64 Cu-liposome and 68 Ga-RGD uptake were moderately correlated, and the authors ultimately concluded only that 68 Ga-RGD does not qualify as a surrogate marker, and that 18 F-FDG (metabolic activity) and 64 Cu-liposome uptake were not correlated. Lee et al 65 introduced 64 Cu-MM-DX-929 (untargeted, no-drug PEGylated liposome) as a universal companion diagnostic agent to prospectively select patients for liposomal therapeutics.…”
Section: Liposomes Theranostic Applications and Diagnostic Techniquesmentioning
confidence: 99%
“…The researchers determined that 64 Cu-liposome and 68 Ga-RGD uptake were moderately correlated, and the authors ultimately concluded only that 68 Ga-RGD does not qualify as a surrogate marker, and that 18 F-FDG (metabolic activity) and 64 Cu-liposome uptake were not correlated. Lee et al 65 introduced 64 Cu-MM-DX-929 (untargeted, no-drug PEGylated liposome) as a universal companion diagnostic agent to prospectively select patients for liposomal therapeutics.…”
Section: Liposomes Theranostic Applications and Diagnostic Techniquesmentioning
confidence: 99%
“…Nanoliposomes could also enhance the stability of the incorporated drugs in vivo, prolong the drug circulation, and readily modify the size and surface to improve the drug’s therapeutic index [ 32 ]. In addition, the EPR effect of radioisotope-loaded liposomes has been clinically proven in metastatic breast cancer patients using positron emission tomography (PET) imaging [ 23 , 33 ]. The advantageous pharmacological properties of liposomal formulations and their clinical applications have been extensively reviewed by Beltran-Gracia et al [ 34 ].…”
Section: Ndds For Chemo- and Immunotherapy Against Nsclcmentioning
confidence: 99%
“…Within nanomedicine, a nanoparticle drug delivery system (NDDS) is a potential solution for overcoming the limitations of anti-cancer drugs, as it can improve the effectiveness of the drugs by increasing the stability and bioavailability, improving transport across the biological barriers and disease targeting, prolonging circulation and blood concentration, reducing enzyme degradation, and reducing the toxicity and immunogenicity of the drugs [ 21 , 22 ]. Nanoparticles are also advantageous to augment the accumulation of therapeutic agents in the cancer tissues via an enhanced permeability and retention (EPR) effect [ 23 , 24 , 25 ]. Many types of nanoparticles have been formulated for the delivery of anti-cancer agents, although only a handful has reached the clinical stage.…”
Section: Introductionmentioning
confidence: 99%
“…These beneficial effects are a result of a phenomenon referred to as Enhanced Permeability and Retention (EPR). EPR is based on the fact that nanodrugs, such as liposomal forms of active substances tend to selectively accumulate in the tissues of solid tumors due to the special properties of blood vessels supplying neoplasms with blood [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%